(untitled) (Revista Peruana de Investigación Educativa, 2012)
The subjectivity of science teachers about their thoughts and actions are evaluative evidence through the recognition of the positions assumed. Science teachers, in this discourse, reveal a state of confusion over terminology and explanatory interpretive frameworks that support their views and assessment practices, which appear as traditional and innovative, without further distinction. These interventions teachers express the reduced effectiveness of the processes of teacher training in the changes promoted, generating, on the contrary, a series of embarrassments in making pedagogical decisions.